DAMPAK COVID-19 TERHADAP PEREKONOMIAN INDONESIA DARI SISI PENDAPATAN NASIONAL PENDEKATAN PRODUKSI - Murdo, Ilham Tri; Affan, Junaidi; Hudaya, Faza (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2022)
The number of Covid-19 cases worldwide continues to show a rapid increase. As of October 31, 2020, the number of cases has reached 45,866,380 and 1,192,684 deaths worldwide, 410,088 people exposed and 13,869 people died in Indonesia. The study aims to determine the extent of the impact of Covid-19 on the Indonesian economy in terms of national income, which is calculated based on the mode of production (business field) Y = ï“ (Pi.Qi)), and predictions in the future, if possible. The Covid-19 pandemic is still going on for a long time. Large-Scale Social Restrictions (PSBB) which were implemented in various regions in Indonesia in April and May, suppressed economic activity in all sectors. Some business sectors have been forced to lay off their employees. Meanwhile, people hold their consumption until conditions are more stable. As a result, Indonesia's economic growth in the second quarter of 2020 contracted by 5.3 percent (YoY). Contribution of corrections came from mining and quarrying (-2.72%), processing industry (6.19%), electricity and gas procurement (-5.46), construction (-5.39%), Wholesale and Retail Trade; Repair of Cars and Motorcycles (-7.57%), Transportation and Warehousing (-30.84%), Provision of Accommodation and Food and Drink (-22.02), company services (-12.09%), and other services ( -12.60%). Then other sectors grew positively in the range of 1.03% -10.88%, with the largest positive growth contribution in the information and communication sector by 10.88%.